Physiochemical, biological, and therapeutic uses of stingless bee honey - Gadge, Ankush S.; Shirsat, Dhananjay V.; Soumia, Parakkattu S.; Pote, Chandrashekhar L.; Pushpalatha, M.; Pandit, Trupti Rajesh; Dutta, Ram; Kumar, Satish; Ramesh, S. V.; Mahajan, Vijay; Karuppaiah, Vadivelu (Frontiers in Sustainable Food Systems, 2024)
Stingless bee honey, also known as pot honey, is a unique product that differs from other honey (Apis) in terms of flavor, chemical composition, biological characteristics, and sourness. Raw and by-products made from this honey have substantial use for its diverse health benefits and human dietary requirements. The physiochemical properties of honey from stingless bee mainly rely on nectar sources, geographic locations, climate, bee species, and handling and storage conditions. The honey contains reducing sugars, water, minerals, and ash content, and its characteristic features include colour, acidity, pH, electrical conductivity, and viscosity. Further, it contains several biological and therapeutic constituents such as flavonoids, antioxidants, antibacterial, wound-healing, antidiabetic, and anticancer properties, and the Maillard reaction product hydroxymethylfurfural. This review summarizes the literature on the physical and biological properties and therapeutic constituents' use of stingless bee honey. It also highlights the quality standards available worldwide and required modifications in establishing universal standards for promoting this honey.